Workers' Perceptions of Occupational Safety and Health at PLTU Bolok Unit II NTT - Elvianus U Lowu; Diana Juniati Nabuasa; Noorce Ch. Berek; Marylin S Junias (Universitas Nusa Cendana, 2021)
Abstract. Employees' perceptions of occupational health and safety (OHS) in a company are significant in preventing accidents and occupational diseases because perceptions affect workers' behavior. This research aims to know factors that affect workers' perceptions about occupational health and safety. This research is an observational study with a cross-sectional design. This research was done in Bolok Electric Steam Power Plan Unit II East Nusa Tenggara with 95 workers. The data analysis used is simple linear regression analysis with α = 0.05 (5%). Based on the study results, the significance of t and the value of experience (5,329 and 0,000) and knowledge (7,034 and 0,000). It shows that experience and knowledge affect employee's perceptions.